Real-time sun protection decisions in first-degree relatives of melanoma patients - Hay, Jennifer L (Health Psychol, 2017)
OBJECTIVE: Melanoma is the most serious skin cancer, and consistent use of sun protection is recommended to reduce risk. Yet, sun protection use is generally inconsistent. Understanding the decisional factors driving sun protection choices could aid in intervention development to promote sun protection maintenance. METHODS: In 59 first-degree relatives of melanoma patients, an interactive voice response system (IVRS) employing participants’ cell phones was used to assess twice daily (morning, afternoon) real-time sun protection usage (sunscreen, shade, hats, protective clothing) and decision factors (weather, type of activity, convenience, social support) over a 14-day summer interval where morning and afternoon outdoor exposures were anticipated. Generalized estimating equations and hierarchical linear models were used to examine the effect of demographics and decisional factors on sun protection choices over time. RESULTS: Sun protection use was inconsistent (e.g., 61% used sunscreen inconsistently). Most strategies were used independently, with the exception of moderate overlap of sunscreen and hat usage. Decision factors were highly relevant for sun protection. For instance, sunscreen use was related to the perception of having adequate time to apply it, whereas shade and hat usage were each related to convenience. Few findings emerged by gender, age, or time of day or year. Significant within-subject variation remained, however. CONCLUSIONS: The findings support continued examination of decision factors in understanding sun protection consistency in real time. Interventions where cues to action and environmental supports work together in varied settings can be developed to improve sun protection maintenance in populations at risk for this common disease.